وظيفة المكان في رواية حكاية حب لغازي القصيبي دراسة وصفية تحليلية: Wadzifah al-Makan fi Riwayah Hikayah Hubb li Gazi al-Qusaibi Dirasah Wasfiyyah Tahliliyyah - Hasdiansyah, Zulfan; Tasnimah, Tatik Mariyatut; Rizqi, Husain Miftahul; Binti R, Siti Rosilawati (Diwan : Jurnal Bahasa dan Sastra Arab, 2024)
تشتمل الرواية الجيدة على عناصر أساسية وهي الشخصيات، الأحداث، الحبكة، الزمان والمكان. ويمتاز لكل عنصر مقومات تفيد غرضا من أغراض الرواية. يهدف هذا البحث إلى معرفة مدى أهمية المكان في بناء الرواية، فقد كانت الرواية تحتوي على عناصر لا يستغني عنها مؤلف الرواية. ومن بين عناصرها ما يقال في علم السردي بالزمكان وهو الزمان والمكان. إلا أن الجانب المكاني لم يعط له الاهتمام عند أكثر الباحثين لأنه بمثابة الزوائد في مجال الرواية. يستخدم الباحثون في هذا البحث المنهج الوصفي في معالجة قضايا السردية حتى يتمكن الباحثون من اكتشاف ظواهرها. ومما يتوصل إليه الباحثون في هذا البحث أن تجلي وظيفة المكان عند توظيف الراوي الأماكن في ثنايا السرد لأغراض شتى بما يدعم الراوي لتفعيل حيوية الرواية Abstract A good novel comprises essential elements such as characters, events, plot, time, and setting. Each of these elements has its components that serve the novel's purpose. This article aims to determine the significance of the setting in novel construction. The novel inherently contains elements indispensable to the author. Among these elements, the concept of "zamakan" in narratology, which refers to time and setting, is pivotal. However, the spatial aspect has not received significant attention from many researchers, often being regarded as supplementary in the context of the novel. This study employs a descriptive method to address narratological issues, enabling researchers to uncover various phenomena. The findings indicate that the function of setting becomes evident when the narrator employs locations within the narrative for various purposes, thereby enhancing the vitality of the novel.